Behavioral Approach, Sharia Business Model Canvas, And Interest in Sharia Fintech Development Among the Millennial Generation - Yesa Cahayaning Ramadhani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
As time goes by, now we have entered the Era of Industrial Revolution 4.0, which is based on technology and the internet in Indonesia, encouraging the growth of innovation and demonstrating digital strategies that are in line with the desires and needs of society at this time, so that it will make it easier for people to carry out financial activities in various economic sectors. , including in the financial sector or what is commonly known as Financial Technology (Fintech). This research aims to test and analyze the Behavioral Approach, CANVAS Sharia Business Model, and Interest in Sharia Fintech Development in the Millennial Generation. The population in this research is fintech users in the millennial generation. The sampling technique was carried out using an accidental sampling technique. The sample that will be selected is the millennial generation. The data obtained is quantitative and this method uses a questionnaire which is measured using a Likert scale. Testing research hypotheses using SEM. The results of the research show that: consumer behavior has a significant positive effect on the development of Sharia fintech in the millennial generation, the canvas business model has a significant positive effect on the development of Sharia fintech in the millennial generation, consumer interest has a significant positive effect on the development of sharia fintech in the millennial generation.